Patterns of Coding in Conversation Texts of the English Zone - Ashari, Erwin (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2015)
The objectives of this study are; (1) to formulate patterns of coding used in conversation texts of the English Zone textbook, 2) to investigate how coding are structured in conversation texts of the English Zone textbook, and 3) to reason why the coding techniques are used in conversation texts of the English Zone textbook. The data were taken from conversation texts of students’ English textbook: English Zone for senior high school students year grade XI (SMA). Descriptive qualitative method was used in this study. There were six conversation texts as the data source was taken from students’ English textbook: English Zone. The findings of this study shown that there are two types of patterns of coding in conversation texts, namely congruent and metaphorical coding. Congruent coding patterns are built in complete mood and residue (at least using mood) and metaphorical coding patterns are built in elliptical mood pattern. Mood and residue pattern is caused by the system of the conversation is using Proposition system. It means the conversation texts involve the statement and question, in another word, the content of the conversation dominantly are about giving and demanding information.  It was found that conversation texts convey the simple structure of conversation which means to attract the readers or students to understand easier by using complete mood and residue and elliptical mood pattern of conversation text is in less number. Thus, those conversation text in English Zone textbook written in simple structures in case of language usage to make the message or information easier to understand. Keywords:English Zone Textbook; Congruent and Metaphor Coding;and Proposition System of Conversation Texts